2021
DOI: 10.1186/s12936-021-03820-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about malaria among Brazilian gold miners in an Amazonian border area: perspectives for malaria elimination strategies

Abstract: Background Mining in the Amazon exposes gold miners to various diseases, including malaria, whose control is still a major challenge. The environment of the mines contributes to the proliferation of vector mosquitoes and the precarious housing conditions facilitate transmission of the disease. Understanding gold miners’ perceptions is essential for the formulation of strategies to fight malaria. A qualitative study was carried out in the municipality of Calçoene, state of Amapá, Brazilian Amazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The evolution of gold miners KAP between 2015 and 2019 shows a significant decrease in the perception of malaria risk and knowledge about the transmission and symptoms of the disease). Another recent study found similar results among gold miners in the FG/Brazil area [ 45 ]. This phenomenon is frequently observed in regions achieving malaria control, due to the reduced contact of the population with the disease [ 20 , 46 ].…”
Section: Discussionsupporting
confidence: 67%
“…The evolution of gold miners KAP between 2015 and 2019 shows a significant decrease in the perception of malaria risk and knowledge about the transmission and symptoms of the disease). Another recent study found similar results among gold miners in the FG/Brazil area [ 45 ]. This phenomenon is frequently observed in regions achieving malaria control, due to the reduced contact of the population with the disease [ 20 , 46 ].…”
Section: Discussionsupporting
confidence: 67%
“…Distribution of preventive measures such as LLINs, LLIHs, and health education in these hotspot municipalities can help reduce malaria transmission in these groups. An earlier study reported Brazilian miners did not know how malaria was transmitted and associated malaria infection with contaminated water and food 37 . In addition, early diagnosis and treatment should be strengthened in mining areas, along with improved regulation of mining activities, which can together make a significant reduction in importation of malaria.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Brazil treatment outside the public sector is prohibited, though there is an informal market for malaria treatment in some municipalities of Roraima, mainly in remote and illegal mining sites. Self-medication is common among miners and could be a problem resulting in an underestimation of actual cases 37 , 38 . Third, important risk factors including education level could not be included in the analysis, since these data were not recorded in Bolivar state.…”
Section: Discussionmentioning
confidence: 99%
“…
Fig. 1 Logic model of the Malakit intervention before the start of the Malakit study [ 10 12 , 14 , 25 27 , 29 – 31 , 35 , 36 ]. Source: created by the authors
Fig.
…”
Section: Main Textmentioning
confidence: 99%